Sensing R-Loop-Associated DNA Damage to Safeguard Genome Stability - Rinaldi, Carlo; Pizzul, Paolo; Longhese, Maria Pia; Bonetti, Diego (Frontiers in Cell and Developmental Biology, 2021)
DNA transcription and replication are two essential physiological processes. Nonetheless, they can turn into a threat for genome integrity, in particular during S phase, when the two processes compete for the same DNA substrate. During transcription a peculiar structure might form, where the nascent RNA strongly binds the template DNA strand and the formation of an RNA-DNA hybrid displaces the non-template single-stranded DNA. This three-stranded nucleic acid transition is called R-loop. The programmed formation of an R-loop plays important physiological functions, but it is now well established that these structures can also turn into a source of DNA damage and genome instability when their homeostasis is altered. Indeed, both their level and distribution in the genome is tightly controlled and the list of factors involved in R-loop regulation is continuously growing. Over the last years, our knowledge about R-loop homeostasis (formation, stabilization, resolution) has definitely increased. However, how they affect genome stability and, especially, how the cellular response to aberrant R-loops is orchestrated are still not fully understood. In this review, we will report and discuss recent findings about this topic and we will focus on R-loop-dependent DNA damage response (DDR) activation through ATR and ATM kinases.